Tourism vocational high school students' and teachers' perception of foreign languages in communicative competencies and the 21st century skills in Yogyakarta - Sufi Indha Akbari (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2018)
This study investigated how is the perception of high school of vocational in tourism program study students in communicating foreign language and revealed the competence in twenty-first century skills. There are about 125 respondents who participated out from 150 survey spread on the vocational high schools that held tourism program study in Yogyakarta involving the teachers and students. The data were collected through comprehensive questionnaire. The results shown that the subjects had following in common and compared result to the teachers shown that perceptual matches and mismatches between the two groups. Through One-Way ANOVA test (P<0.05), there found 7 items in communicative competence that significantly difference in students perception and 18 items on 21st century skills. Meanwhile, the perception between students and teachers, there found 9 items that significantly difference.